The Influence of Metabolic Syndrome on the Development of Gastrointestinal Malignant Tumors—A Review - Vesna Brzački; Andrija Rančić; Snežana Tešić Rajković; Ivan Nagorni; Marko Stamenković; Elena Stanković; Nikola Milutinović; Aleksandar Vukadinović (Medicina)
Background and Objectives: Metabolic syndrome (MetS) is characterized by a cluster of metabolic abnormalities, including abdominal obesity, hyperglycemia, insulin resistance, dyslipidemia, and hypertension. Growing evidence suggests that these components may contribute to the development of gastrointestinal (GI) malignancies. This review aims to explore the association between MetS and GI cancers, including esophageal, gastric, pancreatic, and colorectal cancers. Materials and Methods: A narrative literature review was conducted using PubMed, incorporating 22 sources published between 1991 and 2024. Search terms included “gastrointestinal malignant tumors”, “metabolic syndrome”, “diabetes mellitus”, and “obesity”. Priority was given to large-scale studies from Europe, America, and Asia. Case reports, commentaries, and conference abstracts were excluded. Results: By analyzing the available literature data, this study determined that hyperinsulinemia (IGF-1 pathway), hyperglycemia, and obesity (>102 cm in men and >88 cm in women) are highly associated with the development of esophageal cancer (primarily with Barret’s long and short segment as precancerosis), gastric cancer (through reactive oxygen species), and both pancreatic (1.5–2.4 higher risk) and colorectal cancer (30% higher risk). Patients with a high BMI (>40 kg/m2) show a 20%- or 1.18-times greater risk of developing colorectal cancer and a 1.72-times higher risk of developing pancreatic cancer. There is not enough evidence on the specific influence of hypertriglyceridemia, low HDL cholesterol, and high blood pressure on the development of gastrointestinal malignancy. However, those three conditions have shown a low to moderate association (from 6% to 12%) with the development of colorectal cancer. Conclusions: Metabolic syndrome (MetS) is increasingly being recognized as a significant risk factor for the development and progression of gastrointestinal cancers. Key components such as obesity, hyperglycemia, insulin resistance, and type 2 diabetes mellitus appear to contribute to carcinogenesis through mechanisms involving chronic inflammation, oxidative stress, and immune dysregulation. Further research is needed to clarify the biological pathways linking MetS to gastrointestinal malignancies and to inform effective prevention strategies.